The Liquidity and Liquidity Distribution Effects in Emerging Markets : The Case of Jordan - Vandenbussche, Jerome; Blazsek, Szabolcs; Watt, Stanley (Washington, D.C. : International Monetary Fund, 2009)
This paper analyzes the determinants of daily changes in Jordan's interbank market overnight rate. It not only quantifies the classic liquidity effect, but also uncovers a liquidity distribution effect on both sides of the market, and shows that their magnitude is a decreasing and convex function of the level of excess reserves. It finds that the volatility of rate changes depends much more on the reserve surplus accumulated within a maintenance period than on the level of excess reserves. As Carpenter and Demiralp (2006), it uses the series of the central bank's daily forecast errors to identify the liquidity effect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet